Mini-Bentall procedure for severe aortic regurgitation and root dilation: a case report of rapid recovery, and excellent outcomes - Parama Harta, I Komang Adhi; Sujaya, I Putu Sakamekya Wicakasana (Journal of Indonesia Vascular Access, 2025)
Introduction: The Bentall procedure has long been regarded as the gold standard for addressing combined aortic valve and root pathologies. With advancements in minimally invasive cardiac surgery, the mini-Bentall procedure has emerged as a promising alternative to the traditional approach, offering reduced surgical trauma, shorter hospital stays, and improved postoperative recovery. Case illustration: This report presents the case of a 66-year-old male with severe aortic regurgitation and aortic root dilatation who underwent a successful mini-Bentall procedure. Preoperative evaluation revealed significant left ventricular dysfunction with an ejection fraction of 30.8%, severe aortic regurgitation, and dilatation of the aortic root. The surgery was performed via a mini-sternotomy approach, with careful resection of the aortic root and valve and replacement with a composite graft. Postoperative recovery was uneventful, with minimal bleeding, no mechanical ventilation required, and a significantly reduced length of hospital stay. Conclusion: This case highlights the feasibility and benefits of the mini-Bentall procedure as a less invasive yet effective approach to complex aortic surgery, demonstrating excellent outcomes and rapid recovery.